Intraoperative intravenous dextrose administration and the incidence of nausea and vomiting after gynecologic laparoscopic surgery: a randomized double-blind controlled study - Pin-on, Pathomporn; Boonsri, Settapong; Klanarong, Suwattana (Biomedical Sciences and Clinical Medicine, 2018)
Objective This study tested the hypothesis that administration of intravenous dextrose solution during gynecologic laparoscopic surgery would reduce the incidence and severity of postoperative nausea and vomiting (PONV) compared with an equal volume of normal saline solution Methods A prospective randomized double blind controlled study was conducted. Eighty-six patients were randomized to receive either dextrose solution (n=42) or normal saline solution (n= 44). Bellville postoperative nausea and vomiting scores were recorded for the first 24 hours after surgery. Results Fourteen of 44 patients (31.8%) in the normal saline solution group compared to 15 of 42 patients (35.7%) in the dextrose solution group developed postoperative nausea and vomiting (p =0.09). At each time point, the incidence and severity of PONV were similar. The patients in the dextrose solution group required more postoperative antiemetic medications (p =0.04). Blood glucose levels were significantly higher in the dextrose solution group during both the intraoperative and postoperative periods (p < 0.01). Conclusions Intravenous dextrose administration does not reduce either the incidence or the severity of postoperative nausea and vomiting after laparoscopic gynecologic surgery but it does increase blood glucose level.